Dependency revisited: commodities, commodity-related capital flows and growth models in emerging economies - Michael Schedelik; Andreas Nölke; Christian May; Alexandre Gomes (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
The growth model perspective has provided avenues for bridging comparative and international political economy, mainly regarding the Global Financial Crisis and developments within the eurozone. This article aims to contribute to this endeavor by highlighting the joint effects of capital flows and commodity price swings on growth models in emerging capitalist economies. While the literature on dependent financialization has primarily focused on debt-led growth in the Global South, we spell out the negative implications of commodity-based export-led growth. To this end, we first present a stylized depiction of commodity dependence and provide descriptive statistical evidence of its global prevalence. Subsequently, we trace the co-movement of capital flows to emerging economies and commodity prices. We argue that this 'commodity–finance nexus' reinforces the pro-cyclical nature of commodity-based growth, financial volatility, and the vulnerability to global boom–bust cycles. Furthermore, we demonstrate that the conventional method for establishing growth models by calculating the relative contributions to growth is ill-suited to capture the commodity-based export-led growth model of highly commodity-dependent economies. Finally, we identify commodity price movements and fiscal policies as major drivers of growth, with an important role for domestic politics as an intervening variable.
Keywords: O13; O47; Q33; 330; commodity prices; capital flows; dependent financialization; growth models; emerging economies; boom–bust cycles; export-led growth; fiscal policy; dependency